Extracellular vesicles in bone and tooth: A state‐of‐art paradigm in skeletal regeneration. Issue 9 (7th March 2019) - Jin, Ying; Long, Dan; Li, Juan; Yu, Ruichao; Song, Yueming; Fang, Jie; Yang, Xi; Zhou, Shu; Huang, Shishu; Zhao, Zhihe
Abstract: Bone and tooth, fundamental parts of the craniofacial skeleton, are anatomically and developmentally interconnected structures. Notably, pathological processes in these tissues underwent together and progressed in multilevels. Extracellular vesicles (EVs) are cell‐released small organelles and transfer proteins and genetic information into cells and tissues. Although EVs have been identified in bone and tooth, particularly EVs have been identified in the bone formation and resorption, the concrete roles of EVs in bone and tooth development and diseases remain elusive. As such, we review the recent progress of EVs in bone and tooth to highlight the novel findings of EVs in cellular communication, tissue homeostasis, and interventions. This will enhance our comprehension on the skeletal biology and shed new light on the modulation of skeletal disorders and the potential of genetic treatment. Abstract : Our review will elucidate the newly‐reported exosomes from skeletal systems and highlight their roles in tooth formation, osteogenesis, and osteoclastogenesis, in particular, the potential regenerative therapeutics.